The Influence of Smartphone Usage Duration and Frequency on Smartphone Addiction in Early Childhood Using Binary Logistic Regression - Amalina, Amalina; Samat, N.A; Warmansyah, Jhoni (UIN Imam Bonjol Padang, 2024)
This study aims to identify the influence of smartphone usage duration and frequency on smartphone addiction in early childhood. With the increasing use of technology among children, it is crucial to understand how these factors affect addiction levels. The study employs binary logistic regression to analyze data collected randomly from 100 parents of children aged 4 to 5 years who attend kindergarten in Padang, Indonesia. Smartphone usage duration is measured in hours per day, while frequency of use is measured by the number of uses per day. The analysis results indicate that both the duration and frequency of smartphone use have a significant impact on smartphone addiction. However, based on the odds ratio value, the duration of smartphone use has a more significant influence compared to frequency on addiction levels. These findings provide valuable insights for parents, educators, and policymakers in developing strategies to manage and limit smartphone use in early childhood to prevent addiction risks that could affect their development. This study is expected to serve as a reference for further research and more effective interventions in managing technology use among children.